Blue Carbon Legal Reform in Indonesia: Institutionalizing Seagrass as a Critical Natural Capital - Raia Putri Noer Azzura; Achmad Gusman Catur Siswandi; Yulinda Adharani (Universitas Islam Sultan Agung, 2026)
Blue carbon governance through Presidential Regulation No. 98/2021 and Ministry of Marine Affairs and Fisheries Regulation No. 1/2025 positions seagrass beds as essential carbon sinks for meeting Nationally Determined Contribution (NDC) targets. However, seagrass bed emission baselines have not been standardized within the National Registry System (SRN PPI) due to overlapping regulatory mandates. This situation is exacerbated by a normative antinomy: conservation instruments are sidelined by spatial planning regulations (the Job Creation Law and Government Regulation No. 21/2021) that legalize the conversion of conservation zones for National Strategic Projects (PSN). Using a legal-normative approach, this study finds that these legal contradictions legitimize